(untitled) (Castilla. Estudios de Literatura, 2012)
Angeles Mora’s poetry emerges from the aesthetics of the so called “otra sentimentalidad” to move on to the current of the “poesía de la experiencia”, dominant from the eighties. We cover her poetic path with the aim of show the connections between poetry and history, between poetry and ideology, and we reach to the conclusion that her poetic work means a commitment with the construction of the feminine subjectivity without overlooking her research on the contradictions in individual and collective life.